Health care for patients with hyperglycemia in urgent and emergency situations - dos Santos, Jéssica Batista; Cavalcanti, Emanuele Paula Lopes; Cabral, Ayara Almeida Souza; Sampaio, Thaís Carla Gonçalves; Chagas , Rosa Naiara Cruz; de Oliveira, Leticia Marcelly Lima; da Silva , Ana Claudia Rodrigues; de Oliveira, Nilécia Soares; dos Santos , Roziane Silva; da Costa, Carlos Eduardo (Seven Editora, 2023)
Research Question: What are the nursing care directed to the treatment of patients with Hyperglycemic Emergencies? General and specific objective respectively: Identify in the literature what Hearth care is to be applied in the care of patients with Hyperglycemic Emergencies. Investigate the causes of Hyperglycemic Emergencies. Hypothesis: Health care aimed at treating patients with Hyperglycemic, such as glycemic control through insulin therapy, hydration, hemodynamic monitoring, ICU admission and diagnosis of the cause, favors the normalization of this condition. Type of study: This is a narrative review. DOI: https://doi.org/10.56238/colleinternhealthscienv1-058